2004
DOI: 10.1182/blood-2003-10-3591
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering of coagulation factor VIII for improved secretion

Abstract: Factor VIII (FVIII) functions as a cofactor within the intrinsic pathway of blood coagulation. Quantitative or qualitative deficiencies of FVIII result in the inherited bleeding disorder hemophilia A. Expression of FVIII (domain structure A1-A2-B-A3-C1-C2) in heterologous mammalian systems is 2 to 3 orders of magnitude less efficient compared with other proteins of similar size compromising recombinant FVIII production and gene therapy strategies. FVIII expression is limited by unstable mRNA, interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
198
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(208 citation statements)
references
References 73 publications
5
198
1
4
Order By: Relevance
“…In contrast, a smaller BDD molecule (226/N6, which retains an additional 226 aa with 6 N-linked glycosylation sites from the B domain) is secreted Ϸ10-fold more efficiently than either wtFVIII or BDD, presumably because of increased engagement with the lectin chaperone machinery of the cell (Fig. 1A) (20). wtFVIII, BDD, and 226/N6 each contain eight disulfide bonds so that proper oxidative folding of each of these molecules requires the transfer of 16 electrons from cysteine residues within FVIII to molecular oxygen to form hydrogen peroxide.…”
Section: Compared With Wtfviii and B Domain Deletion 226/n6 Is Morementioning
confidence: 99%
“…In contrast, a smaller BDD molecule (226/N6, which retains an additional 226 aa with 6 N-linked glycosylation sites from the B domain) is secreted Ϸ10-fold more efficiently than either wtFVIII or BDD, presumably because of increased engagement with the lectin chaperone machinery of the cell (Fig. 1A) (20). wtFVIII, BDD, and 226/N6 each contain eight disulfide bonds so that proper oxidative folding of each of these molecules requires the transfer of 16 electrons from cysteine residues within FVIII to molecular oxygen to form hydrogen peroxide.…”
Section: Compared With Wtfviii and B Domain Deletion 226/n6 Is Morementioning
confidence: 99%
“…Plasmid DNA samples (100 mg) were diluted in 2.5 ml lactated Ringer buffer and infused over 10 s into the tail-vein as previously described (Miao et al, 2004). Retro-orbital blood collection was performed at 24 h after injection for measurement of hFVIII activity and antigen in the plasma (Miao et al, 2004).…”
Section: Hydrodynamic Tail-vein Injection and Quantification Of Hfviimentioning
confidence: 99%
“…12 Pipe et al demonstrated that restoration of several N-linked glycosylation sites from the deleted B domain of a B domain deleted (BDD) human (h)-FVIII construct facilitated increased interaction with mannose-binding lectin protein-1 (LMAN1), resulting in more efficient carbohydrate-facilitated transport from the endoplasmic reticulum to the Golgi apparatus. 13 Nathwani et al combined a similar approach with codon optimization and demonstrated significant improvement in FVIII production from liver-directed AAV gene transfer systems. 14 In addition, we have shown that BDD porcine FVIII (p-FVIII) is expressed at 10-to 100-fold greater levels than BDD-h-FVIII in vitro.…”
Section: Origins and Limitations Of Fviii And Fix Biosynthesismentioning
confidence: 99%